Efficacy of axillary dead space closure after mastectomy, axillary clearance and prosthetic reconstruction: a single-center preliminary experience - Lisa, Andrea; Bozzo, Giulia; Vinci, Valeriano; Klinger, Francesco Maria; Errico, Valentina; Tinterri, Corrado; Klinger, Marco Ettore Attilio; Testori, Alberto (Frontiers in Surgery, 2024)
Background Postoperative seroma is most frequent after mastectomy (ME) in combination with axillary lymph node dissection (ALND), and its reported incidence varies from 15.5% up to 90%. Seromas can be responsible for discomfort, infections and can lead to reconstruction failure. Therefore, many ways of seroma prevention have been studied, although from a recent overview it has become clear that no single method is reliably successful. Mechanical closure of the dead space, however, was consistently found to be significantly effective. The aim of our study is to evaluate if quilting of the axilla, in patients undergoing ME, immediate prosthetic breast reconstruction and ALND reduces the duration of drain maintenance, the incidence of seromas that require aspiration (clinically significant seromas, CSS) and reconstruction failure rate. Materials and methods In our study population we analyzed a total of 81 patients divided into two groups: 27 consecutive patients undergoing mastectomy, axillary lymph node dissection (ALND), breast reconstruction and quilting of the axilla. We subsequently randomly picked up a double number of patients (54) undergoing the same oncological and reconstructive procedures without undergoing axillary quilting, matched for clinical characteristics in order to analyze efficacy of the procedure while reducing any bias. Our observational retrospective data was collected from October 2016 to July 2020 in one single high-volume center. Our median follow-up time was of 40.6 months. Results In the case group we observed a reduced time of drain maintenance: 16 vs. 20 days observed in the non-quilted group (p < 0.05). Incidence of seromas that required aspiration was 11% in the control group, while 3,7% in the case group. In addition to that, we observed 6 cases of implant removal in the control group, while in the quilted group we only observed a single case. Conclusion Previous literature and our results confirm that quilting of the axilla with flap fixation significantly decreases time of drain maintenance, allowing the earlier removal of the drains as well as decreasing the incidence of seroma, its eventual associated complications and related social costs. Moreover, our work suggests how quilting sutures decrease the incidence of seroma in patients undergoing immediate reconstruction, probably reducing the risk for implant removal.